PENGENDALI FUNGSI POINTER BERBASIS HAND GESTURE MENGGUNAKAN ALGORITMA CONVEX HULL - Alif Muqtadir; Bambang Pramono; Ika Purwanti Ningrum (semanTIK, 2016)
The development of HCI (Human Computer Interface) has grown more user-friendly. The traditional way of inputting data using keyboard has been replaced gradually since a lot of new method developed. Touch panel developed  from single-touch to multi-touch. Body sense technology even removes obstacles in input device so HCI becomes closer to human nature movement. The most important thing from HCI is manipulating by using hand. The object of this research is to build an application which gives user ability to control pointer by using hand gesture. Method which is used in the application to recognize hand gesture is Convex Hull Algorithm. Convex Hull Algorithm is a method which is used to detect contour or object in image by using points which are connected by lines that cover the contour. The result of this research shows that the application could give the user ability to control the pointer by using hand gesture. Nevertheless, the overall object detections are still needs to  be improved because they are easily distracted by background or object having the same colors as the user’s hand. Keywords— Pointer Controller, Convex Hull, Hand Gesture, Webcam